Beauty pays but does investment in beauty? - Soohyung Lee (IZA World of Labor, 2015)
Being beautiful gives a person an advantage in many settings. Attractive people earn more and have an easier time getting hired. People spend large amounts of money on goods and services to enhance their beauty. Is this enhancement worth pursuing? Research suggests that the expected improvement in beauty from these goods and services is limited. Therefore, despite the large returns from having an attractive appearance, the cost-effectiveness of investment in beauty enhancement is ambiguous. For the average person, the monetary benefits of plastic surgery, medical treatments to increase height, and expensive clothing are not worth the cost.
Keywords: J3; J7; D6; 330; beauty premium; plastic surgery; physical attractiveness; discrimination; height